Tradição em continuidade: monitorização das estratégias bioclimáticas das Quintas no Nordeste Transmontano - Gonçalves, Joana (2015)
In recent decades the vernacular architecture has been recognized as an important source of knowledge in the adaptation of construction to the climate and other specific local characteristics. However, the systematized information is still scarce to quantitatively understand the hydrothermal behaviour of bioclimatic strategies identified in previous surveys to this type of architecture. Using the farmsteads in the northeast region of Portugal as a case study, this article presents the results of hygrothermal monitoring carried out during the heating and cooling seasons. The data obtained enabled to verify and quantify the effective performance of the identified bioclimatic strategies, which are presented as opportunities for contemporary architecture.